The Relationship Between Self-Regulated Learning on Learning Motivation and e-Learning Activities in Virtual Learning at SMAN 9 Tasikmalaya City - Azhari, Septian Cahya; Darmawan, Darwis; Fadjarajani, Siti (Lembaga Riset Mutiara Akbar, 2022)
Virtual learning during the COVID-19 pandemic requires an investigation into the psychological development of students. This study aims to determine the relationship between self-regulated learning on student learning activities using e-learning. This research was conducted in May 2022 on class XI students at SMAN 9 Kota Tasikmalaya by taking a sample of 100 students to fill out a questionnaire. Structural equation modeling partial least square (SEM-PLS) was used to analyze the data in the study. The results showed that the value of the path coefficient of all variables was 0.000 so that there was a significant relationship between self-regulated learning (SLR), learning motivation and e-learning student activity. So to get optimal results during virtual learning, the formation of student SLR is one thing that needs to be focused.